Verteporfin‐Mediated In Situ Nanovaccine Based on Local Conventional‐Dose Hypofractionated Radiotherapy Enhances Antitumor and Immunomodulatory Effect - Zhifan Zhang; Lin Li; Yuchen Ge; Anni Chen; Shanchao Diao; Yueling Yang; Qianyue Chen; Yingling Zhou; Jie Shao; Fanyan Meng; Lixia Yu; Manman Tian; et al. (Advanced Science)
Abstract In situ radiotherapy is the most successful cytotoxic therapy available for the treatment of solid tumors, while high‐dose radiotherapy per fraction is not yet widely and reliably used. To some extent, the major considerations of the disappointing results are on the risk of high‐dose irradiation‐induced damage to the surrounding normal tissues and the difficulty in distant metastasis control. To break these restraints, a gelatinase‐responsive amphiphilic methoxypolyethyleneglycol–PVGLIG–polycaprolactone (mPEG–PVGLIG–PCL) nanoparticles’ loading verteporfin (N@VP), a special photosensitizer that can also be excited by X‐rays to produce cytotoxic singlet oxygen and greatly enhance radiotherapy efficacy, is prepared in this study. Herein, it is shown that the formed N@VP combined with conventional‐dose radiation therapy (RT, 2 Gy (gray, a radiation dose unit)) can realize an antitumor effect no less than high‐dose RT (8 Gy) and minimize radiation dose necessary to achieve local tumor control. Moreover, this radiosensitive nanosystem can exert excellent systemic antitumor immunity and abscopal effect, providing a preferable “in situ vaccine” strategy based on conventional‐dose RT to achieve efficient systemic management of distant tumor metastasis. When combined with immunotherapy, this novel strategy for radiosensitization results in better immunotherapy sensitivity by stimulating significant immunogenic tumor cell death and synergistic antitumor immune responses.